Sensory Nerve Conduction Amplitudes and Z‐Compounds Depend on Body Mass Index in Overweight and Obese Individuals - Sand, Trond; Uglem, Martin; Johnsen, Gjermund; Grøtting, Arnstein; Dunker, Øystein; Sandvik, Jorunn; Nilsen, Kristian B. (Muscle & nerve, 2025)
ABSTRACT Introduction/Aims The association between body mass index (BMI) and nerve conduction study (NCS) amplitudes has not been adequately studied in overweight and obese subjects. Our aim was to estimate the impact of high BMI on NCS amplitudes and NCS summary measures. Methods One hundred and seventy‐five patients with previous gastric bypass surgery and 86 subjects from the general population had clinical evaluations and NCS of upper and lower limbs. Subjects with diabetes, mononeuropathy, or polyneuropathy (PNP) were excluded. Eighty‐three former patients with a mean age of 48 years (SD 8), BMI mean = 34.3 kg/m2 (range 22–60) and 62 control subjects from the general population with a mean age of 55 years (SD 11), BMI mean = 26.6 kg/m2 (range 19–40), were analyzed. Several Z‐compounds were calculated from NCS parameters. Multiple linear regression models compared the impact of BMI on NCS amplitude measurements, corrected for height and age, and NCS‐based Z‐compounds. Results Most sensory amplitudes and tibial nerve motor amplitude decreased significantly with increasing BMI. The magnitudes of association were comparable for BMI and age. A new Z‐compound for sensory amplitudes correlated moderately strongly with BMI for subjects with BMI < 30 kg/m2 and BMI ≥ 30 kg/m2 (standardized beta 0.55 and 0.47 respectively, p < 0.0005). Discussion Sensory NCS amplitudes depend on BMI in obese and non‐obese subjects. Lower reference limits for several sensory amplitudes should probably be adjusted for BMI. Reference limits for amplitude‐dependent Z‐compounds should be corrected for BMI. The findings have relevance for all patients investigated with nerve conduction studies, in particular, patients with suspected axonal polyneuropathies.